Structured object-oriented formal language and method : 9th International Workshop, SOFL+MSVL 2019, Shenzhen, China, November 5, 2019, Revised selected papers /: 9th International Workshop, SOFL+MSVL 2019, Shenzhen, China, November 5, 2019, Revised selected papers. (2020) - Unknown
No abstract available